Investigation of antioxidant effect of pollen in scaly carp (Cyprinus carpio Linnaeus, 1758) in different water temperature - Taskan, Merve; Yonar, Muhammet Enis (Ege Univ, Fac Fisheries, 2023)
In this study, it was aimed to investigate changes in some immunological and antioxidant parameters in scaly carp (Cyprinus carpio) added pollen to their feed in different water temperatures. Fish were stocked to glass aquariums adjusted to 18 degrees C, 23 degrees C and 28 degrees C water temperature. Fish were given diets containing % 2,5 pollen for 14 days. Blood and tissue samples were analysed to determine the immunological parameters and oxidant/antioxidant status. When compared to the control group (23 degrees C), a statistically significant increase in the NBT activity of the groups at 18 degrees C was observed. Decrease in the NBT activity of the group at 28 degrees C was statistically insignificant. The total protein and total immunoglobulin levels of the group at 18 degrees C were decreased, while increase in both parameters at 28 degrees C was not significant. When compared to the control group (23 degrees C), the NBT activity, the total protein and total immunoglobulin levels in the groups that maintained at the same temperature with the control group (23 degrees C) and applied pollen did not show any statistically significant difference. The tissue MDA levels were increased in the groups at 18 degrees C and 28 degrees C when compared to the control group (23 degrees C). The tissue MDA levels of the groups treated pollen simultaneously with the change in temperature were lower than the groups at 18 degrees C and 28 degrees C. The tissue GSH levels and GST activities were decreased in the groups at 18 degrees C and 28 degrees C when compared to the control group (23 degrees C). The tissue GSH levels and GST activities of the groups treated pollen simultaneously with the change in temperature were higher than the groups at 18 degrees C and 28 degrees C. In conclusion, stress caused by temperature differences in fish may be prevented by pollen.
Keywords: Antioxidants; immunity; fish; oxidative stress; temperature